Impact of non-pharmacological interventions on activity limitations and participation restrictions in older breast cancer survivors: A scoping review. Issue 2 (March 2022) - Brick, Rachelle; Turner, Rose; Bender, Catherine; Douglas, Madilyn; Eilers, Rachel; Ferguson, Robert; Leland, Natalie; Lyons, Kathleen D.; Toto, Pamela; Skidmore, Elizabeth
Abstract: Cancer-related disability is a complex problem for older breast cancer survivors. One aspect of cancer-related disability is a survivor's inability to complete meaningful daily activities and engage in life roles, referred to as activity limitations and participation restrictions respectively. There is a limited understanding of how interventions influence activity limitations and participation restrictions in this population. A scoping review was undertaken to identify and characterize nonpharmacological interventions developed to address activity limitations and participation restrictions. A systematic search of electronic databases (Ovid Medline, Embase, EBSCO CINAHL, and Ovid PsycINFO) was conducted in April 2020 and updated October 2020. Eleven studies met inclusion criteria. Most frequently observed delivery features were in-person and one-on-one format. Six interventions incorporated telehealth delivery components. Interventions were often complex and varied in content. Exercise and behavioral strategies were among the most frequently used active ingredients. Activity limitations and participation restrictions were often secondary outcomes, and measures of these outcomes were varied in content and assessment method. Study samples were not representative of the current population of older adult breast cancer survivors. Future intervention research should clarify intervention delivery, content, and dose, prioritize comprehensive measurement of activity limitations and participation restrictions, as well as recruit and involve representative study samples to enhance generalizability of findings.